2011
DOI: 10.1590/s1516-89132011000100004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro multiplication of 'Flordaguard' rootstock: cytokinin source and concentration effects, explants orientation and period of permanence in the culture medium

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…BAP is responsible for cell division, overcoming apical dominance, and induction of the proliferation of axillary buds (MOK et al, 2000). The present results are similar to those observed by Moraes et al (2004) in Pyrus calleryana D-6 and Radmann et al (2011) in the rootstock 'Flordaguard' (Prunus persica L. Bastch). Both studies found that in the absence of BAP, the emission of new shoots does not take place, creating a dependency on the addition of exogenous cytokinin for the induction of shoots in these two Rosaceae species.…”
Section: +supporting
confidence: 87%
“…BAP is responsible for cell division, overcoming apical dominance, and induction of the proliferation of axillary buds (MOK et al, 2000). The present results are similar to those observed by Moraes et al (2004) in Pyrus calleryana D-6 and Radmann et al (2011) in the rootstock 'Flordaguard' (Prunus persica L. Bastch). Both studies found that in the absence of BAP, the emission of new shoots does not take place, creating a dependency on the addition of exogenous cytokinin for the induction of shoots in these two Rosaceae species.…”
Section: +supporting
confidence: 87%
“…The reason behind this is that the composition of nutrient media is in agreement with the plant growth requirements. As the shoot multiplication under in vitro condition is largely depends on plant genotype and cytokinins concentration (Radmann et al, 2011) so cytokinins concentration in medium must be optimized in order to get effective shoot proliferation (Khan et al, 2010). According to the results, cultivar "BARI Zaitoon-2" performed better under different cytokinins concentrations by having more shooting percentage (%) and number of shoots per explant.…”
Section: Methodsmentioning
confidence: 99%
“…Pérola and Imperial cultivars were provided by the EMBRAPA Tabuleiros Costeiros (Aracaju, SE, Brazil). The micropropagation was carried out using MS medium (Murashige and Skoog 1962) without growth phytoregulator as described by Corrêa et al (2009), Quoirin et al (2008), Radmann et al (2011) and Scherwinski-Pereira et al (2009). The MS medium was supplied with 30 g/L of sucrose and 7 g/L of agar-agar.…”
Section: Micropropagationmentioning
confidence: 99%